Relationships among carcass characteristics of cattle exhibited at shows in the Midwest - McKee, M.; Schalles, R.R.; Harris, M.; Zoellner, K.O.; Westmeyer, H.W. (Kansas State University. Agricultural Experiment Station, 2011)
Carcass data were collected from 24 carcass shows held throughout the Midwest, including eight county shows in Kansas and one county show in Nebraska, seven years’ results from the Kansas National Junior Livestock Show in Wichita, two years results from the Midwest Steer and Carcass Show at Austin, Minn,. two years results from the St. Joseph Live Steer and Carcass Show, St. Joseph, Mo., and one-year results from AK-SAR-BEN, Omaha, Nebr., Waterloo Carcass Show, Waterloo, Iowa; Hoosier Beef Show, Indianapolis, Ind.; and the 4-H Beef Carcass Summary, Nebraska State Fair, Lincoln, Nebr.
Keywords: Beef; Carcass characteristics; Carcass weight; Rib-eye